2023
DOI: 10.1111/anae.16120
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative tobacco cessation interventions: a systematic review and meta‐analysis

S. Harrogate,
J. Barnes,
K. Thomas
et al.

Abstract: SummaryTobacco smoking is associated with a substantially increased risk of postoperative complications. The peri‐operative period offers a unique opportunity to support patients to stop tobacco smoking, avoid complications and improve long‐term health. This systematic review provides an up‐to‐date summary of the evidence for tobacco cessation interventions in surgical patients. We conducted a systematic search of randomised controlled trials of tobacco cessation interventions in the peri‐operative period. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…As the studies demonstrated better postoperative pain among former smokers compared to current smokers, this suggests smoking cessation or reduction would be of benefit by allowing for better short-term pain management and improved postoperative outcomes [38]. A recent systematic review by Harrogate et al assessing perioperative smoking cessation interventions highlights the effectiveness these programs have at facilitating smoking cessation, both at the time of surgery and 12 months after surgery [39]. In addition, patients with chronic pain and long-term opioid use may benefit from pain clinic referrals prior to surgical intervention to optimise their analgesic use and consider attempting opioid weaning [40].…”
Section: Discussionmentioning
confidence: 99%
“…As the studies demonstrated better postoperative pain among former smokers compared to current smokers, this suggests smoking cessation or reduction would be of benefit by allowing for better short-term pain management and improved postoperative outcomes [38]. A recent systematic review by Harrogate et al assessing perioperative smoking cessation interventions highlights the effectiveness these programs have at facilitating smoking cessation, both at the time of surgery and 12 months after surgery [39]. In addition, patients with chronic pain and long-term opioid use may benefit from pain clinic referrals prior to surgical intervention to optimise their analgesic use and consider attempting opioid weaning [40].…”
Section: Discussionmentioning
confidence: 99%
“…Strengths include this being among the largest of all perioperative cessation trials. 4 Inclusion of all eligible smoker is another as it showed the real effect of the intervention on a population. Trials randomising only after consenting comprise the vast majority of studies, 7 19 yet may overestimate the incentive population effect by including subsets with better prognostic features.…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 However, such studies show great heterogeneity and further studies are needed to determine cessation strategies that are acceptable, effective and easily incorporated into elective surgical pathways. 4 Because longer cessation confers greater benefits, we previously trialled whether offering free mailed nicotine replacement therapy (NRT) plus telephone Quitline referral at time of wait-listing for elective surgery increased perioperative abstinence. 5 6 When offered this help, between 32% 6 and 39% 5 of smokers requested it (costing approximately $A70 (£37, €42, US$45) per acceptance), resulting in approximately doubling verified abstinence compared with standard care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Musallam reported that smoking cessation at least one year before a major surgery reduces the risk of postoperative mortality [ 12 ]. The evidence from a systematic review and meta-analysis of 38 randomised controlled trials suggests that perioperative SCIs lead to an increase in abstinence rates for up to 12 months following the surgical procedure [ 13 ]. The current evidence-based interventions for smoking cessation encompass behavioural treatments, quit lines, web-based support services, and pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%